The Influence of Institutional Ownership on Firm Value with Dividend Policy and Investment Decisions as Intervening Variables (a Study on Consumer Goods Companies on the Indonesia Stock Exchange) - Cahyaningtyas, Berlin My Anggelita Pramesthi; Anwar, Muhadjir (PT FORMOSA CENDEKIA GLOBAL, 2024)
Performance is measured by company valuation to attract investors. This study examines the effects of institutional ownership on firm value in three ways: 1) directly, 2) indirectly with dividend policy as an intervening variable, and 3) indirectly with investment decisions as an intervening variable. From 279 consumer goods manufacturing companies listed on the Indonesia Stock Exchange until 2023, 52 were selected via purposive sampling. Using the Sobel Test, it was found that: 1) Institutional Ownership positively and significantly impacts Firm Value, 2) Dividend Policy does not mediate the effect of Institutional Ownership on Firm Value, and 3) Investment Decisions do mediate the effect of Institutional Ownership on Firm Value